1990
DOI: 10.1104/pp.94.3.996
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Uptake and Starch Biosynthesis by Slices of Developing Maize Endosperm

Abstract: 14C-Sugar uptake and incorporation into starch by slices of developing maize (Zea mays L.) endosperm were examined and compared with sugar uptake by maize endosperm-derived suspension cultures. Rates of sucrose, fructose, and D-and L-glucose uptake by slices were similar, whereas uptake rates for these sugars differed greatly in suspension cultures. Concentration dependence of sucrose, fructose, and D-glucose uptake was biphasic (consisting of linear plus saturable components) with suspension cultures but line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In vitro studies of sugar influx by exposed endosperm of developing maize kernels suggested that sugar influx occurred by passive diffusion alone (Griffith et al 1987). However, this behaviour could result from mechanical damage to the uptake mechanism (Felker et al 1990; Thomas et al 1992). The developing wheat grain appears to be a more robust experimental model.…”
Section: Filial Transport Mechanismsmentioning
confidence: 99%
“…In vitro studies of sugar influx by exposed endosperm of developing maize kernels suggested that sugar influx occurred by passive diffusion alone (Griffith et al 1987). However, this behaviour could result from mechanical damage to the uptake mechanism (Felker et al 1990; Thomas et al 1992). The developing wheat grain appears to be a more robust experimental model.…”
Section: Filial Transport Mechanismsmentioning
confidence: 99%
“…High levels of invertase activity localized at the base of a kernel have been demonstrated (Shannon, 1972), and the resulting hexose may be phosphorylated and enter the starch pathway independently of SS (Dohlert et al, 1988;Felker et al, 1990). However, it has also been shown that hydrolysis of SUC is not an absolute requirement for movement of SUC into the endosperm (Schmalstig and Hitz, 1987).…”
Section: Starch Biosynthesismentioning
confidence: 99%
“…Felker et al (1990), using maize endosperm tissue slices, also suggested that hexose may enter the starch biosynthetic pathway, but tissue slices may not necessarily represent in vivo conditions. The questions of whether hexose is phosphorylated and then converted to starch in the amyloplast or if UDP-Glc is a critica1 metabolite in the starch biosynthetic pathway remain points of discussion.…”
mentioning
confidence: 99%